Tanzania Agriculture Public Expenditure Review - World Bank; FAO (Washington, DC, 2022)
The World Bank and FAO teamed up with the Government of Tanzania to produce the country’s first agricultural public expenditure review (PER) since the launch of the country’s second agriculture sector development program (ASDP II). After outlining the role and performance of the sector (crop, livestock, fisheries, and forestry) in Tanzania and its main policy frameworks, this report uses historical data from 2017 to 2022 to review the level and composition of public expenditure. It then analyzes its allocative efficiency, effectiveness and alignment with the Government’s strategic sectoral goals as defined in Tanzania Vision 2025 and the ASDP II. To do so, it combines a price incentive analysis on key value chains, thematic deep dives on strategic areas for the government (irrigation, agricultural knowledge system, seed system, climate change adaptation), and a coherence analysis. The report unveils that agricultural public budget mostly targets public goods in Tanzania, but at a level too critically low for these to materialize and support sustainable productivity growth and job creation. Detailed actionable recommendations are proposed for the government to improve spending on the agricultural sector to leverage further its growth potential.